Mechanical differences of sickle cell trait (SCT) and normal red blood cells1. Issue 15 (7th August 2015) - Zheng, Yi; Cachia, Mark A.; Ge, Ji; Xu, Zhensong; Wang, Chen; Sun, Yu
<x xml:space="preserve">Abstract</x> Shear modulus and viscosity of sickle cell trait red blood cells and normal RBCs were measured under controlled oxygen conditions.